Marina. - Borovik, Samira; Tomic, Marina (s.l. : DAI / ArtEZ, Institute of the Arts, 2009)
Bernstein, Ana ; Borer, Alain ; Borovik, Samira ; Cohen, Renato ; Goldberg, Roselee ; Turner, Victor
This booklet is part of a growing collection of artists publications issued by the Dutch Art institute (DAI), produced in collaboration with the Werkplaats Typografie and edited by artist/curator Delphine Bedel
boek